2018
DOI: 10.1039/c7cp05911f
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water on the physicochemical properties of an ethylene glycol and choline chloride mixture containing Cu2+ ions: electrochemical results and dynamic molecular simulation approach

Abstract: The effect of water on the physicochemical properties of an ethylene glycol and choline chloride mixture containing Cu2+ ions was investigated by electrochemical techniques and molecular dynamics simulation. The experiments and computational calculations were carried out by increasing the water content from 0 up to 10% (v/v). The cyclic voltammetry and chronopotentiometry techniques showed that the diffusion coefficient of Cu2+ ions increased and that the peak potentials for both the Cu2+/Cu+ and Cu+/Cu redox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…However, RTILs are sometimes toxic and un-Moreover, ChCl-based DESs are highly hygroscopic. The strong influence of H 2 O on the viscosity and conductivity of the solvents has been reported in many occasions 15,[21][22][23] . More recently, it has also been shown that water affects the dynamics and the electrochemistry of active species 15,21,24,25 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, RTILs are sometimes toxic and un-Moreover, ChCl-based DESs are highly hygroscopic. The strong influence of H 2 O on the viscosity and conductivity of the solvents has been reported in many occasions 15,[21][22][23] . More recently, it has also been shown that water affects the dynamics and the electrochemistry of active species 15,21,24,25 .…”
Section: Introductionmentioning
confidence: 93%
“…Two sets of the most commonly used and studied DESs 14,16,[20][21][22]24,38,39,44,[49][50][51][52] were prepared by mixing and stirring choline chloride (ChCl) (VWR Life Sciene, high purity) with: 1) urea (U) (Merck KGaA, 99.5%), and 2) ethylene glycol (EG) (Merck KGaA, 99.5%) in a 1:2 molar ratio, respectively, at 80 • C for 1 h. To minimize water content when needed, choline chloride and urea were dried at 80 • C for 12 h in a vacuum oven prior to their use. After obtaining homogeneous and transparent solvents, 0.2 M of NiCl 2 •6H 2 O (Merck KGaA, 98%) was added.…”
Section: Electrolyte Preparationmentioning
confidence: 99%
“…The increase in water fraction up to 75 wt % leads to a three-fold increase in thermal conductivity. Bezerra et al explored the effect of water on the electrochemical behavior of Ag+ ions in reline by combining experiments and MD simulations [280]. Using the cyclic voltammetric technique, it was demonstrated that the addition of water catalyzes the electrochemical reduction of Ag + ions in reline DES.…”
Section: Effects Of Water On Relinementioning
confidence: 99%
“…16 In order to overcome poor physical properties in DESs, the addition of water has been investigated. 12,[17][18][19][20] Computer simulations have revealed that the addition of water, to ethaline or reline DESs, decreases the number of hydrogen bonds formed and consequently lowers the viscosity of both DES systems. 20 However, as more water is added, it has been observed 12 that ChCl-based DESs start to lose their DES structure, and form aqueous solutions, above a 1 : 1 equivalent of water:chloride.…”
Section: Introductionmentioning
confidence: 99%
“…12,[17][18][19][20] Computer simulations have revealed that the addition of water, to ethaline or reline DESs, decreases the number of hydrogen bonds formed and consequently lowers the viscosity of both DES systems. 20 However, as more water is added, it has been observed 12 that ChCl-based DESs start to lose their DES structure, and form aqueous solutions, above a 1 : 1 equivalent of water:chloride. This transition is also reported to change the electrochemical properties of ChCl-based DESs, in particular, by narrowing their potential window.…”
Section: Introductionmentioning
confidence: 99%